(untitled) (CIPEEX, 2025)
The use of illicit substances can cause alterations in the Central Nervous System (CNS), constituting a global public health issue. In addition to brain damage, the consumption of these substances may lead to physical, psychological, social, occupational, and legal consequences. Objective: To assess the use of licit and illicit drugs among workers in the São Patrício Valley, Goiás, and its association with sex. Method: This is a cross-sectional, quantitative study conducted with workers in the São Patrício Valley, approved by the Ethics Committee (CEP) under protocol no. 6,436,246. The sample consisted of 804 participants, of whom 63.7% were female. The block of questions related to alcohol, drug, and tobacco use from the National School Health Survey (PeNSE) was applied. Data were analyzed using SPSS software, version 23.3, and the Chi-square test was used to compare variables. A p-value < 0.05 was considered statistically significant. Results: Among respondents, 84.7% reported having consumed alcoholic beverages at some point in their lives, 28% reported having smoked at least one cigarette, and 7.6% reported having used drugs. When comparing between sexes, men reported higher consumption in the last 30 days of cigarettes (p < 0.001) and drugs (p < 0.001) compared to women. Regarding alcohol consumption, no significant difference was found between sexes (p = 0.207). Conclusion: Alcohol consumption showed the highest prevalence among substances, with no difference between sexes. Male workers reported higher consumption of cigarettes and illicit drugs. Therefore, it is necessary to develop and implement public policies to reduce alcohol and tobacco consumption among workers, especially men, since the use of these substances can cause numerous short-, medium-, and long-term health and quality of life impairm